The preschool's direct and indirect effects in Brazil - Reyna, Edi Flores (2023)
Interventions in early childhood, like preschool education, have several effects on individuals' outcomes. We can observe preschool's impact on schooling, health outcomes, educational attainment, workforce productivity, and future wages. However, the preschool's effect can also identify in intra-household relationships. For example, in the household, the child's preschool attendance may impact the time allocation of the family members, especially the person who take-care the child. Furthermore, the relationships between the child and her parents may be affected by the learning obtained in preschool. Therefore, in this doctoral dissertation, we sought to identify preschool's effects on intra-household relationships from Brazilian families. This dissertation has been divided into two chapters to understand these effects better. In the first chapter, we aim to identify whether preschool attendance may influence the children's bargaining power in the family decision-making process. To do so, we exploit the educational reform caused by the Brazilian Constitutional Amendment N° 59 of 2009 and the CNE/CEB Resolution N° 2/2016, which makes preschool attendance mandatory from 4 years old onwards. We drew our analysis sample from the POF 2017-2018. Due to the characteristics of the data, the identification strategy we used was a randomization-based RDD approach. We found evidence that preschool frequency can affect the children's bargaining power in family decision- making. Namely, preschool improves the children's bargaining power in the family decision- making process by approximately 0.22 and 0.29 standard deviation in purchasing products of interest to children. We infer, therefore, that preschool attendance affects children's role in family decision-making through improved human capital. Furthermore, we corroborated that children should indeed be considered in household demand analysis. On the other hand, in the second chapter, we focus on identifying the indirect effects of preschool on intra-household variables related to maternal labor supply, the older sibling's domestic, productive work, and the demand for education for older siblings. In this chapter, we also exploit the same preschool educational reform. However, the database comes from the Household Sample Survey (PNAD) for 2011-2015. Using this data, we apply the fuzzy estimation's standard RDD (under the assumption of continuity). Results show that the child's attendance at preschool increases the mother's average weekly working hours by 26 hours but does not affect the hours offered by older siblings in the labor market. In addition, the intervention increases the older siblings'household chores in low-income families. Concerning older siblings' education attendance, the younger child's preschool attendance showed adverse effects; the preschool reduces the school attendance of the older sibling. This effect is heterogeneous when considering the older siblings' sex: girls are more affected than boys. Finally, the results identify the substitution effect of time allocation between the mother and the older sibling. Keywords: Preschool. RDD approach. The family decision-making process. Labor market outcomes. Household chores.